Integration of Discount Strategies, Digital Promotion, and Customer Engagement in Enhancing MSME Competitiveness in the E-Commerce Ecosystem During Ramadan - Azzaakiyyah, Hizbul Khootimah; Suherlan; Rijal, Syamsu (Technology and Society Perspectives (TACIT), 2025)
Competition in the e-commerce ecosystem intensifies during Ramadan, particularly for MSMEs that must compete with large corporations. This study aims to analyze how the integration of discount strategies, digital promotion, and customer engagement can enhance the competitiveness of MSMEs in the e-commerce ecosystem during Ramadan. Using a literature review approach with a descriptive qualitative method, this research examines various studies from Google Scholar and credible websites from the 2021–2025 period. From an initial selection of 30 articles, a rigorous screening process was conducted, resulting in 22 relevant articles. The findings indicate that discounts can attract customer attention, but their effectiveness heavily depends on the right digital promotion strategy and active customer engagement. MSMEs that successfully leverage social media, live shopping, and data-driven marketing strategies have proven to be more competitive in attracting and retaining customers. Case studies such as Rendang Minang Rajo, Buttonscarves, and Somethinc demonstrate that the combination of discounts, digital marketing strategies, and strong customer interaction can significantly boost sales during Ramadan. The implications of this study highlight the importance of utilizing digital technology and data-driven marketing strategies for MSMEs to remain competitive in an increasingly saturated market.